Introducing Novitates Paleoentomologicae: An outlet for occasional fossil insect research at the University of Kansas - Engel, Michael S.; McKellar, Ryan C; Ortega-Blanco, Jaime (Novitates Paleoentomologicae, 2013)
A new journal is introduced which disseminates the results of research conducted at or in association with the University of Kansas on fossil insects and their relatives. The journal spans all aspects of paleoentomological research, extending beyond systematic studies to include works on insect-bearing deposits, and their taphonomy and ecology.